RESEARCH-AI résumés: learning to improve self-presentation for the labor market - LeFebvre, Luke; LeFebvre, Renée A. (Frontiers in Education, 2025)
Career readiness is central to job placement, and the development of a competitive résumé by students plays a crucial role in that process. Thus, institutions of higher education have introduced résumé AI tools to help prepare students for the workforce. AI résumé tools are software applications used to optimize résumés. This study explores students’ (N = 88) perceived usefulness of résumé AI tools and examines how these tools contributed to student learning and teaching. The results demonstrate that a majority (70.5%) of students found AI résumé tools advantageous for improving their résumés. Future research should explore how humans interpret and integrate the algorithmic feedback generated by résumé AI technology to effectively adapt their résumés.